Analysis of vegetable juice-based medium components for the induction of Candida filamentation - Valles Muela, Jannys Gabriela (2024)
Candida is the most common genus of unicellular pathogenic fungi and is responsible for a wide variety of human infections. The ability of this fungus to induce a “morphological change", transforming yeast-like cells to filamentous cells, is a virulence factor linked to its pathogenicity. In this study, the induction of filamentation in Candida was investigated using vegetable juice-based culture media inspired by commercial V8 juice. In addition, the morphogenesis process was examined for each vegetable separately, and other modulating factors, such as pH, temperature and concentration, were analyzed. The results suggest that individual vegetables alone can induce standard filamentation in Candida, supporting the hypothesis that this fungus could have an origin as a plant symbiont or pathogen. Future research is proposed to explore the metabolic pathways involved in filamentation, using mutants of known transcription factors and reporter genes. This would provide a molecular basis for the regulation of Candida filamentation in vegetable media. Furthermore, this could have important implications for explaining the mechanisms of fungal filamentation in vegetables and their transition to humans. This study not only offers insights into the biology of Candida in relation to vegetables but also lays the foundation for the development of safer and more stable culture media that reduce the risk of false positives and disease transmission, as well as new approaches for antifungal treatments.